2000
DOI: 10.1103/physrevb.62.7571
|View full text |Cite
|
Sign up to set email alerts
|

Carbon nanotubes: From molecular to macroscopic sensors

Abstract: The components that contribute to Raman spectral shifts of single-wall carbon nanotubes ͑SWNT's͒ embedded in polymer systems have been identified. The temperature dependence of the Raman shift can be separated into the temperature dependence of the nanotubes, the cohesive energy density of the polymer, and the buildup of thermal strain. Discounting all components apart from the thermal strain from the Raman shift-temperature data, it is shown that the mechanical response of single-wall carbon nanotubes in tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
117
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(122 citation statements)
references
References 10 publications
5
117
0
Order By: Relevance
“…11 G-band shape changes are reported while doping, 19 applying pressure 21 and changing the surrounding medium. 23 The influence of the environment on the G band might be unexpected at first. But all carbon atoms of SWCNTs are on the surface and, as a result, the G band is sensitive to the environment.…”
Section: Dmentioning
confidence: 99%
See 2 more Smart Citations
“…11 G-band shape changes are reported while doping, 19 applying pressure 21 and changing the surrounding medium. 23 The influence of the environment on the G band might be unexpected at first. But all carbon atoms of SWCNTs are on the surface and, as a result, the G band is sensitive to the environment.…”
Section: Dmentioning
confidence: 99%
“…Large shifts (20 cm 1 ) of the G 0 2D band in SWCNTs have been reported in the literature. 23 We compare spectra of CNTs in methanol and air when using a low laser power (Fig. 1).…”
Section: Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have shown that the addition of a small volume fraction of CNTs to various polymers can improve the bulk modulus of the composite materials such as epoxy [5], polyimide [6], polyethylene [7], methyl-ethyl ethacrylate [8], or polyvinyl alcohol [9]. Additionally, the large electrical and thermal conductivities of carbon nanotubes have lead to the creation of unique nanocomposites that can quickly dissipate electrostatic charges [10] or withstand high temperatures with minimal mechanical degradation [11]. Since the first reported work on CNT-reinforced polymer nanocomposites materials [12], they have found widespread application in automotive, aerospace, defense, sporting goods, infrastructure, and medical sectors [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers are applying this phenomenon using various materials systems with a range of electrically conductive fillers. The materials systems, which are being investigated in this study, are thermoplastics, [1][2][3][4][5][6][7][8][9][10][11][12] thermoset resins, 13,14 and cement. 15 Of the various types of nanofillers, carbon nanotubes (CNTs) are the dominant choice when conductivity is necessary, because they provide high strength and modulus at low concentration.…”
Section: Introductionmentioning
confidence: 99%